Turning analysis into action: opportunities and challenges in implementing wastewater science for public health decision-making - Anna Gitter; Anna Gitter; Valeria Ruvalcaba; Katelyn Clark; Katelyn Clark; Theresa Tran Carapucci; Theresa Tran Carapucci; Theresa Tran Carapucci; Fuqing Wu; Fuqing Wu; Blake M. Hanson; Blake M. Hanson; et al. (Frontiers in Public Health)
In the 5 years since the emergence of the COVID-19 pandemic, the field of wastewater-based epidemiology (WBE) has dramatically expanded with programs implemented across the globe to monitor for SARS-CoV-2 and other viruses of public health concern. However, the best way to use wastewater surveillance data and inform local communities of the utility of wastewater science remains limited and sporadically discussed. Specifically, there is vague guidance regarding interpreting varying levels of viral loads in wastewater for public health significance. While collaborative efforts are key to implementing these community-specific wastewater surveillance programs, effectively using the data for public health decision-making still needs significant refinement. Aligned with recent calls for advancing the science of wastewater surveillance, the experiences described in this article examine the critical need to advance other aspects of WBE programs, including communication, ethics, and decision-making.